Commuters, Wanderers, and 'international Mongrels': Resistance and Possibility in Post-immigrant Literature - (:unkn) unknown (My University, 2017)
The recognizable motifs of the immigrant tale have been upended, as the traditional narrative has been adapted to capture the multitude of directions, individuals, nations, and paths of the twenty-first century migrant. In four chapters, I examine selected works from the authors Colum McCann, Junot Díaz, Jhumpa Lahiri, and Chimamanda Ngozi Adichie to argue for a new designation, “post-immigrant literature.” Post-immigrant literature treats critically the themes of loss, regret, and forced assimilation from perspectives shaped by post-colonial, post-modern and post-identity politics thinking. Rather than narratives stressing the limitations imposed by deterministic social forces, post-immigrant texts posit more agency, and anxiety, for their transnational characters. Post-immigrant literature departs from preceding generations by proffering possibility, empowering the subject, creating space for more voices, and disrupting traditional binaries, expectations or assumptions. Ultimately, I argue that the post-immigrant narrative detangles the strands of immigrant literature and disavows the “single story” so as to appropriately represent individuality.
Keywords: Adichie; Diaz; Immigrant; Lahiri; Mccann; Post-immigrant